ANALISIS JARINGAN KOMUNIKASI PADA PENGEMBANGAN PERTANIAN ORGANIK DI KOTA KENDARI - Rahayu Endah Purwanti; Darsilan Dima; Vit Neru Satrah; Yusriadin Yusridin; Pertiwi Syarni; Normal Bivariant Padangaran (Jurusan Penyuluhan Pertanian FP UHO, 2025)
The issue of sustainability is currently a very important issue in agricultural development. Organic farming is an application of a sustainable agricultural system. The back to nature lifestyle has become a trend for some people. However, the phenomenon encountered in the field is that there are still many organic farmers who have not fully implemented organic farming cultivation techniques in accordance with the Indonesian National Standard (SNI) issued by the Indonesian National Standardization Agency (BSN) and the adoption of innovations also seems slow. This study was conducted to describe the tendency of communication network patterns in farmer women's groups so as to accelerate the process of diffusion of innovations related to the development of organic farming in Kambu District, Kendari City. The specific objectives were: (1) analyzing the role of each key informant; (2) knowing the pattern of communication networks formed in organic farming development activities. This research is a survey research using quantitative analysis. The research location is in Kambu Sub-district, Kendari City, Southeast Sulawesi Province. Data collection was conducted through surveys, in-depth interviews, focused discussions and observations. Sample determination in this study is by census. Data analysis was descriptive. The results obtained in this study are that in the KWT Manggarai communication network there are three cliques in the form of fingers centered on one individual and spread to members. The specific functions found in the KWT Manggarai communication network are star, opinion leader, liaison officer, bridge, and no isolate. The average degree of connectedness in the KWT Manggarai communication network system is 21.33 and is classified as very good.